Drivers of Green Entrepreneurial Intention: Why Does Sustainability Awareness Matter Among University Students? - Prabowo, Hartiwi; Ikhsan, Ridho Bramulya; Yuniarty, Yuniarty (Frontiers in Psychology, 2022)
Entrepreneurship is an essential aspect in economic growth due to its contribution to people's welfare through employment opportunities. Universities offer compulsory entrepreneurship subjects for students with the support of government policies. Therefore, this study aimed to determine the factors that influence students' intentions to become green entrepreneurs using contextual aspects as moderators. The applied theoretical model was the planned behavior (TPB) that adds cultural values and cognitive knowledge. The sample included 305 students from private universities in Jakarta. The results showed that green entrepreneurial intentions are affected by perceived behavioral control, cultural values, and cognition knowledge. However, they lack a significant effect on attitudes toward behavior and subjective norms. Second, contextual factors can moderate the relationship between variables and significantly affect green entrepreneurial intentions. Third, they moderate attitudes toward behavior and cognitive knowledge with green entrepreneurial intentions. Contrastingly, other factors had no effect when contextual factors moderated the relationship